Amlodipine effect as a trigger factor for massive growth of giant gingival overgrowth: A case report - Ibriana, Ibriana; Zulistiana, Ditha; Nurfaizah, Tira; Oktawati, Sri (Journal of Case Reports in Dental Medicine, 2024)
Introduction: Drug-induced gingival overgrowth has been widely reported, especially in hypertensive patients. Amlodipine is a type of hypertension drug that often triggers gingival overgrowth. This case is made worse by poor oral hygiene conditions which cause massive growth and enlargement of the gingiva.Â Case Report : A 63 year old man came to Hasanuddin University Dental and Oral Hospital with complaints of enlarged gums in the palate area and right cheek. The patient suffers from hypertension and has been regularly taking amlodipine for the past 1 year. Enlarged gums make it difficult for patients to clean their teeth and mouth, resulting in patients experiencing bad breath and difficulty chewing on the side that they complain about due to loose teeth. Enlarged gums are not painful, but often bleed when touched by a toothbrush or food.Conclusion : Treatment of gingival overgrowth by substitution of hypertension drugs, strict oral hygiene control, and surgical intervention through gingivectomy and flap surgery procedures showed satisfactory results after 5 months of follow-up.